2004
DOI: 10.1007/s00586-004-0682-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical perspectives on secular trends of intervertebral foramen diameters in an industrialized European society

Abstract: Low back pain originshave been a matter of great controversy. While spinal stenosis is now radiologically traceable, the alteration of intervertebral foramen is less clear. The aim of this study was to assess "secular trends" -alterations occurring from one generation to the next -in osseous intervertebral foramina of the major vertebral segments in an industrialized society, and to discuss their possible clinical implication. The macerated "maximum intervertebral foramen width" and "intervertebral foramen hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…Nevertheless, this study hopefully contributes valuable osteometric data on the age-related changes of the human spinal morphology. Our approach links anthropological and clinicalanatomical research, as done previously (Rühli et al, 2002;2004), and it may help to further decipher the equivocal findings of the impact of age, especially nondegenerative normal aging, on the human spinal morphology.…”
Section: Alterations Of Stature and Robustnessmentioning
confidence: 96%
“…Nevertheless, this study hopefully contributes valuable osteometric data on the age-related changes of the human spinal morphology. Our approach links anthropological and clinicalanatomical research, as done previously (Rühli et al, 2002;2004), and it may help to further decipher the equivocal findings of the impact of age, especially nondegenerative normal aging, on the human spinal morphology.…”
Section: Alterations Of Stature and Robustnessmentioning
confidence: 96%
“…In particular, secular trends in spinal dimensions and pathology were reported (Henneberg and Henneberg, 1999;Hukuda et al, 2000;Jankauskas, 1994;Rothschild and Rothschild, 1996;Rü hli, 2003;Rü hli and Henneberg, 2004;Rü hli et al, 2002;Stefko, 1926;Tatarek, 2001). Spinal measures, including spinal cord dimensions, were also assessed with a special focus on their size in relation to body or brain size (Elliott, 1945;Latimer, 1950;MacLarnon, 1996b; …”
Section: Introductionmentioning
confidence: 92%
“…More spinal data on past populations will enable more detailed and complex assessment of human evolutionary trends such as bony gracilization (Schwidetzky, 1962) and adaptations of human head shape and brain size (Henneberg, 1988;Weidenreich, 1945;Wiercinski, 1979). Finally, secular trends in spinal dimensions have only recently begun to be addressed (Clark et al, 1985;Jankauskas, 1994;Rü hli and Henneberg, 2004;Tatarek, 2001), and an increase in available cross-temporal and cross-population spinal data will be highly valuable for further exploration of these issues. Only dry bone samples can contribute such valuable long-term information.…”
Section: Significance For Physical Anthropologymentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, the maximum diameters of IVF estimated in case IA, case IIA and case IIB was found to be much reduced (Table 1), when compared to normal standard IVF dimensions of cervical region. 16 Further, in case III of cervico-thoracic synostosis, due to asymmetric fusion of vertebrae, the left IVF was found to be much narrowed (Table 1) causing ipsilateral neurological symptoms due to left spinal nerve involvement.…”
Section: Resultsmentioning
confidence: 91%